Adaptation of Islamic Law through Gotong Royong Tradition in Minority Communities of Tomohon and Tana Toraja - Bilalu, Naskur; Jamal, Ridwan; Subeitan, Syahrul Mubarak; Purwadi, Wira; Gómez, José Manuel Naranjo (Institut Agama Islam Negeri (IAIN) Manado, 2024)
This research explores the adaptation of Islamic law through local wisdom, particularly the gotong royong tradition, in Muslim minority communities in Tomohon and Tana Toraja. Using a qualitative approach and case study method, the research involved 20 informants, including Islamic religious leaders, traditional leaders, and active Muslim community members. The findings show that the gotong royong tradition facilitates the practice of Islamic law in marriage, zakat management, and religious celebrations by integrating the values of inclusivity and local cultural solidarity. Harmony is created through intensive dialogue between Islamic and Christian religious leaders, strengthening interfaith relationships. Adjustments, such as the use of moderate adhan volume and distribution of zakat to all levels of society regardless of religion, serve as tangible evidence of this adaptation. This research contributes to the development of Fiqh Nusantara, demonstrating the flexibility of Islamic law that can align with local culture while supporting social inclusion. Practically, these results provide insights for policymakers to design policies that support religious harmony in multicultural regions. This research affirms that Islamic law not only maintains its essential teachings but can also become an integral part of pluralistic society. The implications of this research open opportunities for further studies on the harmonization of Islamic law in other minority communities.